Factors that affect student engagement in online learning in health professions education. (March 2022) - Elshami, Wiam; Taha, Mohamed H.; Abdalla, Mohamed Elhassan; Abuzaid, Mohamed; Saravanan, Coumaravelou; Al Kawas, Sausan
Abstract: Background: Student engagement is vital in achieving learning outcomes and improving students' motivation, involvement, and attitudes toward learning. The aim of this study was to identify the factors that affect student engagement in online learning in medical and health science colleges. Methods: A cross-sectional study was conducted among medical and health science students and faculty in May 2020. The Online Engagement Strategies Questionnaire was e-mailed to 370 students and 102 faculty members. The SPSS statistical software was used for the statistical analysis. Exploratory factor analysis was performed to identify the factors that affected the students' engagement in online learning. Composite scores were calculated for factors, separately for the student and faculty responses. Descriptive statistical analysis was performed for the student and faculty responses. Results: The response rates of the students and faculty were 85.1% and 74.1%, respectively. The mean ages of the students and faculty were 20.6 and 44.6 years, respectively. Eighty-five percent of the faculty ( n = 51) and 88.3% ( n = 278) of the students found that the use of technology in proper communication was an important strategy to engage students in online learning. The factor analysis revealed agreement between the students and faculty regarding the factors that support student engagement in online learning. Techno-pedagogical skills were considered very important for faculty and important for students. For both faculty and students, self-directed learning skills were important, and peer-assisted learning (PAL) was fair symmetry. Nevertheless, collaborative learning (CL) was fairly symmetry to students and important to faculty. Conclusion: To enhance student engagement in online learning, faculty members should consider improving their techno-pedagogical skills. Moreover, by incorporating self-directed learning, CL and PAL will support student engagement. Finally, faculty development, updating of course design, and institutional policies are all required to support online learning.